The Detailed Assessment of Posttraumatic Stress–Second Edition (DAPS-2): Initial Psychometric Evaluation in an MTurk-Recruited, Trauma-Exposed Community Sample. (September 2020) - Petri, Jessica M.; Weathers, Frank W.; Witte, Tracy K.; Silverstein, Madison W.
The Detailed Assessment of Posttraumatic Stress (DAPS; Briere, 2001) is a comprehensive questionnaire that assesses posttraumatic stress disorder (PTSD) diagnostic criteria as well as peritraumatic responses and associated problems such as dissociation, suicidality, and substance abuse. DAPS scores have demonstrated excellent reliability, validity, and clinical utility, performing as well or better than leading PTSD questionnaires. The present study was an initial psychometric evaluation of the unreleased DAPS (DAPS-2), revised for Diagnostic and Statistical Manual of Mental Disorders–Fifth edition ( DSM-5 ), in an MTurk-recruited mixed trauma sample ( N = 367). DAPS-2 PTSD scale and associated features scales demonstrated high internal consistency and strong convergent and discriminant validity. In confirmatory factor analyses, the DSM-5 four-factor model of PTSD provided adequate fit, but the leading seven-factor model provided superior fit. These results indicate the DAPS-2 is a psychometrically sound measure of DSM-5 PTSD symptoms.